Development of a Medium Voltage, High Power, High Frequency Four-Port Solid State Transformer - El Shafei, Ahmad; Ozdemir, Saban; Altin, Necmi; Jean-Pierre, Garry; Nasiri, Adel (CES Transactions on Electrical Machines and Systems, 2022)
The power and voltage levels of renewable energy resources is growing with the evolution of the power electronics and switching module technologies. For that, the need for the development of a compact and highly efficient solid-state transformer is becoming a critical task in-order to integrate the current AC grid with the new renewable energy systems. The objective of this paper is to present the design, implementation, and testing of a compact multi-port solid-state transformer for microgrid integration applications. The proposed system has a four-port transformer and four converters connected to the ports. The transformer has four windings integrated on a single common core. Thus, it can integrate different renewable energy resources and energy storage systems. Each port has a rated power of 25kW, and the switching frequency is pushed to 50kHz. The ports are chosen to represent a realistic industrial microgrid model consisting of grid, energy storage system, photovoltaic system, and load. The grid port is designed to operate at 4.16kVAC corresponding to 7.2kV DC bus voltage, while the other three ports operate at 500VDC. Moreover, the grid, energy storage and photovoltaic ports are active ports with dual active bridge topologies, while the load port is a passive port with full bridge rectifier one. The proposed design is first validated with simulation results, and then the proposed transformer is implemented and tested. Experimental results show that the designed system is suitable for 4.16kVAC medium voltage grid integration.